Information security handbook - Zaman, Noor, 1972-; Hussain, Khalid; Humayun, Mamoona; Abdullah, Azween Bin, 1961-; Tavares, João Manuel R. S. (Internet of everything (IoE). Security and privacy paradigm., 2022)
"This handbook provides a comprehensive collection of knowledge for emerging multidisciplinary research areas such as cybersecurity, IoT, Blockchain, Machine Learning, Data Science, and AI. This book brings together in one resource Information security across multiple domains. Information Security Handbook addresses the knowledge for emerging multidisciplinary research. It explores basic and high-level concepts, serves as a manual for industry, while also helping beginners to understand both basic and advanced aspects in security-related issues. The handbook explores security and privacy issues through IoT ecosystem and implications to the real world and at the same time explains the concepts of IoT-related technologies, trends, and future directions. University graduates and postgraduates, as well as research scholars, developers, and end-users, will find this handbook very useful"--